A Review of Small Farmer Land Use and Deforestation in Tropical Forest Frontiers: Implications for Conservation and Sustainable Livelihoods - David López-Carr (MDPI AG, 2021)
Forest conversion for agriculture is the most expansive signature of human occupation on the Earth’s surface. This paper develops a conceptual model of factors underlying frontier agricultural expansion—the predominant driver of deforestation worldwide—from the perspective of small farm households—the majority of farmers globally. The framework consists of four causal rubrics: demographic, socioeconomic, political–economic, and ecological. Following this approach, the article explores the current state of knowledge on tropical deforestation in tropical agricultural frontiers with a focus on Latin America, the region of greatest deforestation worldwide during recent decades. Neo-Malthusian arguments notwithstanding, in many tropical nations, deforestation has proceeded unabated in recent years despite declining rural populations. However, evidence from the global-to-household scale suggests that population size and composition are also related to farm forest conversion. Existing particularist or behaviorialist theories sometimes fail to capture key geographical and temporal dimensions, yet studies support the notion that certain cultural, individual, and household characteristics are crucial determinants of forest clearing. Conversely, while institutional arguments sometimes fail to emphasize that the ultimate land use change agents are local resource users, their livelihood decisions are shaped and constrained by policies governing economic subsidies, and market and infrastructure development. Further, although ecological change is usually modeled as an outcome in the deforestation literature, increasingly acute climate change and natural farm endowments form a dynamic tabula rasa on which household land use decisions are enabled. To more fully comprehend frontier forest conversion and to enhance protection and conservation while promoting vital local livelihoods, future research may fruitfully investigate the interaction of demographic, social, political, economic, and ecological factors across spatial scales and academic disciplines.